Gender-Affirming Pharmacological Interventions for Youth With Gender Dysphoria: When Treatment Guidelines Are Not Enough. (November 2017) - Nahata, Leena; Chelvakumar, Gayathri; Leibowitz, Scott
Youth with gender dysphoria, also known as transgender youth, are increasingly presenting to multidisciplinary clinics within academic pediatric centers across the United States. Gender-affirming pharmacological interventions for adolescents with gender dysphoria may be used to promote positive psychological well-being and mental health outcomes. Interventions range from completely reversible to partially irreversible, based on the age and sexual maturity of the adolescent. For each intervention, dilemmas and controversies exist regarding age at treatment initiation, treatment duration, safety, and cost. Pharmacists' awareness of these considerations and interventions is important when providing evidence-based gender-affirming care to this underserved population.